2020
DOI: 10.1039/d0ra00138d
|View full text |Cite
|
Sign up to set email alerts
|

Novel organic–inorganic hybrid powder SrGa12O19:Mn2+–ethyl cellulose for efficient latent fingerprint recognitionviatime-gated fluorescence

Abstract: A easy and efficient strategy for latent fingerprints recognition was developed by this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…In contrast, the 4 T 2 → 4 A 2 transition is expected to have a much shorter decay time (microsecond range). Thus, the broadband emission arises from the spin-forbidden 2 E → 4 A 2 transition, contrary to previous reports. Xu et al report decay time in the ms range for the SrGa 12 O 19 :Cr 3+ phosphor at 750 nm, although the exact decay time and absence of corresponding structural information make further comparison difficult. Similarly, a decay time of ∼2 ms is observed for the Cr 3+ –Cr 3+ ion pair in the Cr 3+ -doped LaAlO 3 perovskite material .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the 4 T 2 → 4 A 2 transition is expected to have a much shorter decay time (microsecond range). Thus, the broadband emission arises from the spin-forbidden 2 E → 4 A 2 transition, contrary to previous reports. Xu et al report decay time in the ms range for the SrGa 12 O 19 :Cr 3+ phosphor at 750 nm, although the exact decay time and absence of corresponding structural information make further comparison difficult. Similarly, a decay time of ∼2 ms is observed for the Cr 3+ –Cr 3+ ion pair in the Cr 3+ -doped LaAlO 3 perovskite material .…”
Section: Resultsmentioning
confidence: 99%
“…The magnetoplumbite type structures with formula A [ B 12 ]­O 19 offer an opportunity for a stronger Cr 3+ –Cr 3+ ion pair signal due to the availability of five independent crystallographic sites for the B site cation, where cation B may have valence ranging from 2+ to 5+. , Therefore, the magnetoplumbite type structure provides a versatile host system in which to tune luminescent optical properties. For example, Xu et al reported SrGa 12 O 19 :Cr 3+ (λ em = 750 nm) for long-persistence applications, while the narrowband green-emitting SrGa 12 O 19 :Mn 2+ (λ em = 505 nm) is integrated with ethyl cellulose for the latent fingerprints visualization in anticounterfeiting applications . Similarly, LaMgAl 11 O 19 :Cr 3+ (λ em = 698 nm) is co-doped with Yb 3+ ions for the requirements of emission at 980 nm in solar energy conversion .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… [ 126 ] Tb doped gadolinium aluminate nanophosphors (GdAlO 3 :Tb 3+ ) -Yield a correct picture of the entire fingerprint with excellent accuracy and contrast. [ 127 ] -Highly efficient -Fast SrGa 12 O 19 :Mn 2+ -Strong chemical stability [ 128 ] -Can last up to months -All 3 levels of LFP could be obtained favourabling selectivity. NaYF 4 :Yb,Er,Gd fluorescent upconversion nanorods (UCNRs) -Great performance with excellent sensitivity.…”
Section: Reuse Applications For the Spent Adsorbentsmentioning
confidence: 99%
“…e sensitivity of fluorescence detection usually is high even when the concentration of the analytes is very low. For example, quantum dots [26][27][28], metal colloids [29], and fluorescent upconversion nanoparticles [30][31][32] have been successfully utilized for the visualization of fingerprints [33][34][35][36]. However, typical fluorescent materials are usually monochromatic, which are difficult to be applied to the object with complex multicolor background and hard to distinguish the difference between fingerprint lines and multicolor background [34].…”
Section: Introductionmentioning
confidence: 99%